Faktor Pendukung dan Penghambat Proses Pemberdayaan Perempuan melalui Budidaya Jahe dan Lengkuas (Studi Kasus CSR PT. Combiphar) - Sulistyaningrum, Dian; Sugihardjo, Sugihardjo; Ihsaniyati, Hanifah (AGRITEXTS: Journal of Agricultural Extension, 2024)
The women’s empowerment program through ginger and galangal cultivation was initiated by Corporate Social Responsibility (CSR) of Combiphar Inc. This program aims to improve the welfare and capacity of women farmers. Initially, this program was welcomed enthusiastically by members of the target women’s farmer groups (KWT), but there was a decline in KWT member participation in the second planting period. This research aims to determine the supporting and inhibiting factors in the process of empowering KWT Karya Makmur II in ginger and galangal cultivation carried out by CSR of Combiphar Inc. This research uses a descriptive qualitative analysis method with a case study approach. In this research, the informants involved included members of KWT Karya Makmur II, the Persada Yogyakarta Foundation as Combiphar’s partner, the Agriculture and Food Service, Field Agricultural Extension Officers (PPL), as well as the local community. Data collection techniques were carried out using in-depth interviews, observation and documentation as well as using Miles and Huberman’s interactive analysis. The research results show that leadership, cooperation, policy and technology are supporting factors in the empowerment process of KWT Karya Makmur II in ginger and galangal cultivation. Meanwhile, inhibiting factors include dependency, commitment, organizational management, and marketing. Research findings reveal that the success of empowerment programs depends not only on technical factors but also on social and institutional factors. This provides important recommendations for further CSR program development, namely the need for a holistic approach that takes into account socio-economic aspects and institutional capacity in community empowerment efforts.